2008
DOI: 10.1111/j.1444-2906.2008.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slaughter methods on physical, biochemical and microbiological quality of rainbow troutOncorhynchus mykissand mirror carpCyprinus carpiofilleted in pre-, in- or post-rigor periods

Abstract: Rainbow trout Oncorhynchus mykiss and mirror carp Cyprinus carpio were slaughtered by either percussion or asphyxiation. For determination of the physical (texture value) and biochemical quality attributes [pH, lactic acid, total volatile basic nitrogen (TVB-N), and malondialdehyde (MDA) values] of trout and carp, the fish were filleted immediately (within 2 h), 12 h after harvest (pre-rigor), 24 and 36 h after harvest (in-rigor), and finally 48 and 60 h after harvest (post-rigor). For microbiological quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 41 publications
4
23
0
5
Order By: Relevance
“…Throughout the chilled storage, higher mean TBA-i values were obtained in most cases in samples belonging to the post-RM condition; however, differences were not found to be significant (p > 0.05). In agreement with the present research, lower TBA-i values were reported for fillets obtained from pre-RM rainbow trout and carp than in their post-RM counterparts (Duran et al, 2008). …”
Section: Assessment Of Interaction Compound Formationsupporting
confidence: 81%
See 1 more Smart Citation
“…Throughout the chilled storage, higher mean TBA-i values were obtained in most cases in samples belonging to the post-RM condition; however, differences were not found to be significant (p > 0.05). In agreement with the present research, lower TBA-i values were reported for fillets obtained from pre-RM rainbow trout and carp than in their post-RM counterparts (Duran et al, 2008). …”
Section: Assessment Of Interaction Compound Formationsupporting
confidence: 81%
“…However, the quality analysis has mainly been focused on sensory and physical properties, while lipid damage differences have been scarcely studied (Antipova and Smirnova, 1982;Duran et al, 2008). The present work concerns the lipid damage (hydrolysis and oxidation) development of Chilean jack mackerel during chilled storage.…”
Section: Lipid Oxidation Analysismentioning
confidence: 99%
“…On the contrary, Duran et al (2008) found that slaughter method (asphyxia or percussion) had no effect on the MDA values of carp (Cyprinus carpio). However, when considering rainbow trout (O. mykiss) the MDA content of flesh from fish slaughtered by asphyxiation was significantly higher than that of specimens slaughtered by percussion (4 and 3 mg MDA/kg flesh, respectively).…”
Section: Killingmentioning
confidence: 82%
“…The quality of the fish quick setback took place after the fish die due to several factors, among others, the enzymatic process, or the presence of spoilage microorganisms that develop in the body of the fish. Biochemical changes and microbial postharvest in fish tissue is highly dependent significantly on factors that control the concentration of substrate and metabolites associated with microbial contamination and the condition after the arrest [1]. Good fresh fish handling needs to be done to maintain the level of freshness of the fish and extend shelf life.…”
Section: Introductionmentioning
confidence: 99%